Effect of Ridogrel on Vascular Contractions Gaused by Vasoactive Substances Released during Platelet Activation - Janssens, W J; Cools, F J S; Hoskens, L A M; Van Nueten, J M (Thrombosis and Haemostasis, 1990)
Ridogrel (6.3 × 10−6 to 10−4 M) inhibited contractions of isolated rat caudal arteries and rabbit femoral arteries caused by U-46619. The slope of an Arunlakshana-Schild plot (pA2-value: 3.4 × 10−6 M) on the caudal artery was slightly higher than one (1.14). This effect was maximal within}D min of incubation of the blood vessel with the compound and easily reversible. Ridogrel antagonised contractions of isolated rabbit femoral arteries caused by prostaglandin Fzo2α in the same concentration range. Ridogrel also inhibited contractions induced by aggregating rat platelets on isolated rat caudal arteries (itt the presence of ketanserin 4 × 10−7 M) and on isolated rabbit pulmonary and femoral arteries (in the absence of ketanserin). Ridogrel had no effect on Ca2+-induced contractions in depolarised isolated rabbit femoral arteries, and at 10−4 M antagonised serotonin-induced contractions in this blood vessel. Its effect on serotonin-induced contractions was statistically significant but very small on isolated rat caudal arteries. These observations indicate that ridogrel is an antagonist of prostaglandin endoperoxide/thromboxane A2 and prostaglandin F2α raCeptors on vascular smooth muscle.